WHAT IS THE ROLE OF ADVANCED NURSE PRACTITIONERS (ANPs) IN A MAJOR TRAUMA TEAM (MTT)?. Issue 9 (14th August 2014) - Adkins, Charlotte V; Trivedy, Chetan; Stanhope, Benjamin
Abstract : Objectives & Background: ANPs are autonomous practitioners and form a core part of many Emergency Departments (EDs). However, there is little data on their role in major trauma and deployment within MTTs. The project aimed to explore clinicians' views on the role of ANPs within MTTs in Major Trauma Centres (MTCs). Methods: A two-part project using an anonymised questionnaire was designed to explore attitudes towards the role of ANPs as part of the MTT. Part one was distributed to members of the MTT at an MTC in the West Midlands (the author's workplace); using an online survey tool, part two was sent to the clinical leads of all 26 MTCs in England. Resultant data includes current national use of ANPs in MTTs, reasons for inclusion/exclusion, and understanding, attitudes and opinions regarding their involvement. Results: At the author's workplace, 93% of responses felt that ANPs should form part of an MTT (remaining 7% unsure). Data suggests that there is a lack of understanding of the ANP role (45% stating they fully understand the role, 55% partially) and of ANP training in regard to managing major trauma, with resultant uncertainty regarding abilities. 76% feel ANPs should have a role in clinical assessment of patients, 68% that they should have a role in breathing interventions (ie manual ventilation) and 90% circulatory interventions (cannulation/pelvic splint application). 85% of national MTCs responded; 81% of these have ANPs in their ED but only 11% utilise ANPs as a core MTT member. Where ANPs are part of the MTT, their roles tend to be in line with normal nursing roles (ie circulatory interventions 100%, drug preparation/administration 50%). Only 50% of respondents utilised ANPs for clinical assessment, part of their day-to-day role. 13% felt that ANPs do not have a role in MTTs. Barriers to ANP involvement include rota capacity (35%), clinical competence (25%), training priorities (22%), supervision (16%), ANP training (52%), ability (68%) and skills (36%). Conclusion: The project data shows that, although ANPs are now part of many ED teams and are increasingly taking on extended autonomous ED roles, there is still a level of uncertainty and lack of clarity on their role as part of an MTT. There needs to be a national policy outlining and standardising ANP training, qualification and utilisation within the ED as well as a robust programme to promote their education, training and skills, to optimise their deployment.